Elbow Arthroplasty: From Normal to Failure - Levin, Elizabeth S.; Plotkin, Benjamin (Seminars in Musculoskeletal Radiology, 2019)
Total elbow arthroplasty is currently an established surgical treatment for several pathologies of the elbow. Although initially used primarily in the treatment of rheumatoid arthritis, indications for total elbow arthroplasty have expanded and now include trauma, primary and secondary osteoarthritis, fracture nonunion, and following neoplasm resection. Desired outcomes of elbow arthroplasty include decreasing patient pain, restoration of function and mobility, and prevention of or treatment for instability. In comparison with total elbow arthroplasty, radial head replacements are most commonly performed following trauma. An additional technique, capitellar resurfacing arthroplasty, was developed in an effort to prevent early-onset osteoarthritis secondary to altered elbow biomechanics following radial head replacement. Complications of these surgeries include loosening, fracture, instability and dissociation, bushing wear, and particle disease.
Keywords: elbow arthroplasty; radial head replacement; capitellar resurfacing; elbow joint